The Impact of Climate Change on Waterborne Microbial Diversity and Dysbiosis in Carcinogenesis of Indian Sundarbans Fisherpersons: A Review - Saha, Sanjib; Basu, Biswarup (Research Advances in Environment, Geography and Earth Science Vol. 2, 2024)
Fishing is one of the employment-generating as well as fastest growing sectors and has an important role in socio-economic development in India. Approximately 4 lakh fishermen directly, and 6 lakhs indirectly engage and depend on this industry in West Bengal. Indian Sunderbans lies in North & South 24 Parganas districts and has faced major cyclone shocks of Amphan, Bulbul, Yaas, and Fani within a span of the last 5 years and huge cultivable and livable areas went into the water. Recent reports reveal that these 2 districts have the highest cancer registry in West Bengal. Fishing involves physical hazards, chemical hazards, and biological hazards and it is of national interest to estimate post-climate change chemical and biological effects on affected fisherpersons. Our project would look into pre and post-climate change data from primary health centers and identify affected areas and fisherpersons following questionnaires and health checkups. Reported occupational health hazards and precancerous lesions from the affected population will be further analyzed along with the quality of water-in-use or contact, and residing pathogenic or carcinogenic microbes whether correlated with dysbiosis, direct or zoonotic pathogenesis, etc. This will be the first of a kind of work connecting affected fisherpersons, the quality of their used waterbodies affected by climate change, the rising cancer scenario, and occupational health hazards in Indian Sundarbans. Climate anomalies (salinity, anoxic conditions, and temperature) in waterbodies favor pathogens to grow rapidly that affect fisherperson’s health through opportunistic invasion directly or through zoonotic transmission resulting in waterborne diseases. Such waterborne infection is linked to increased gastric and gynecological cancer risk by dysbiosis of gut microbiota (producing toxins and metabolites). The goal of this review paper is to suggest a baseline regarding the alteration of climate that may induce factors of dysfunction that may prevalence of cancer (skin, uterine, gastric) in fishermen who are in direct contact with saline water.